White Matter Matters: Unraveling Violence in Psychosis and Psychopathy. Issue 1 (30th June 2021) - Tesli, Natalia; Rokicki, Jaroslav; Maximov, Ivan I; Bell, Christina; Hjell, Gabriela; Gurholt, Tiril; Fischer-Vieler, Thomas; Bang, Nina; Tesli, Martin; Westlye, Lars T; Andreassen, Ole A; Melle, Ingrid; et al.
Abstract: Individuals with psychotic disorders have an increased risk of committing acts of violence. Neurobiological support for the extent to which violence in psychosis is driven by psychotic symptoms and/or antisocial traits could have clinical and legal implications. Neuroimaging studies have reported white matter (WM) abnormalities in individuals with psychosis and in those with antisocial traits. However, it is unknown whether WM abnormalities in psychosis patients with a history of violence (violent-PSY) resemble those found in nonviolent psychosis patients (nonviolent PSY), violent nonpsychotic individuals (violent non-PSY), or both. Diffusion tensor imaging scans from 301 males including violent-PSY ( n = 28), violent non-PSY ( n = 20), nonviolent PSY ( n = 58), and healthy controls (HC, n = 195) were analyzed with tract-based spatial statistics. Fractional anisotropy (FA), mean, axial and radial (RD) diffusivity were compared between groups. Psychopathic traits in the violent groups were measured with Psychopathy Checklist-revisited (PCL-R). Violent-PSY had globally lower FA and higher RD, compared with nonviolent PSY. Both psychosis groups and violent non-PSY group had widespread disruptions in WM compared with HC. There were no significant WM differences between violent-PSY and violent non-PSY. PCL-R scores did not differ between the violence groups and were associated with higher RD in corpus callosum. Here we demonstrate a widespread pattern of reduced WM integrity in violent-PSY compared with nonviolent PSY. The lack of significant WM and PCL-R differences between the violence groups, together with the positive association between PCL-R and WM deficits in violent-PSY and violent non-PSY may indicate shared neurobiological underpinnings of trait violence.